Economic Analysis of Applying Biomass Stove to Produce Hot Water Serving Child Development Center: The Case Study Of Omkoi District, Chiangmai, Thailand - Chulasak, R; Phothachareon, W; Sawatdeenarunat, C (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2019)
This research aims to perform the techno-economic feasibility of the applied hybrid biomass stove to produce hot water for serving Child Development Center (CDC) in Omkoi District, Chiang Mai, Thailand. The hot water generated from the stove could help to decrease LPG usage and enhance household economics. Many activities in CDC (i.e., children showering during the winter season, cloth washing, and utensils cleaning among others) require hot water to prevent the contamination of harmful germs which could cause many diseases such as diarrhea in young children. Presently, Asian Development College for Community Economy and Technology, Chiang Mai Rajabhat University (adiCET) has installed the hybrid stove to the in Omkoi district. The biomass stove could generate 90 °C hot water using plant/agriculture waste as the fuel. However, the economical parameters (i.e., Payback Period, Net Present Value and Internal Rate of Return) could strengthen the technology. The results from this study could be used as one of the guidelines for policymakers to design the appropriate programs for enhancing the CDC using the waste-to-energy concept.